New soliton solutions of the system of equations for the ion sound and Langmuir waves - Demiray, Şeyma Tülüce; Bulut, Hasan (My University, 2017)
This study is based on new soliton solutions of the system of equations for the ion sound wave under the action of the ponderomotive force due to high-frequency field and for the Langmuir wave. The generalized Kudryashov method (GKM), which is one of the analytical methods, has been tackled for finding exact solutions of the system of equations for the ion sound wave and the Langmuir wave. By using this method, dark soliton solutions of this system of equations have been obtained. Also, by using MathematicaRelease 9, some graphical simulations were designed to see the behavior of these solutions
Keywords: Fizik; Atomik ve Moleküler Kimya